Penggunaan Merek tidak Sesuai Dengan Merek yang Didaftarkan (Studi Kasus Antara PS GLOW Melawan MS GLOW) - Hasan, Umar; Maryanti, Fifin (Wajah Hukum, 2024)
It often happens that trademarks are used that are not in accordance with those registered, which can lead to trademark infringement lawsuits. An example of this case is the dispute between PS GLOW and MS GLOW at the Surabaya Commercial Court. The method in this research uses a statutory approach with a duration of 6 months, focusing on the problem of using brands that are not in accordance with those registered, especially in the case of PS GLOW versus MS GLOW. The primary legal material used is Law Number 20 of 2016 concerning Trademarks and Decision Number 2/Pdt.Sus.HKI/Merek/ 2022/PN. Niaga Sby, secondary legal materials include related books and articles. The research was carried out in the literature using data collection techniques through document study and the data analysis was qualitative analysis, which in this research was only in the form of narratives. The result was a case between PS GLOW and MS GLOW related to trademark infringement in accordance with Article 83 Paragraph (1) of Law no. 20 of 2016. The panel of judges decided that MS GLOW illegally used a brand similar to PS GLOW, as stated in Decision Number 2/Pdt.Sus.HKI/Merek/2022/PN.Niaga Sby on 12 July 2022. This decision was based on expert statement stating that the use of unregistered marks is not protected by law so it can lead to infringement lawsuits and reflects bad faith, so clear regulations regarding the use of marks are needed.